Urban regimes in comparative perspective: the politics of urban development in Britain - Digaetano Alan; Llemanski John S.
Untill now urban regime analyst focussed almost entirely on cities in the United States. In this article the author broaden the definition of urban regimes to fit the British urban experience, then seek to trace the formation of regimes in Birmingham and Bristol during the 1980s. The formulation and implementation of specific economic development strategies and policies for each of these two cases is detailed, and finally an evaluation of regime capacity for each is explored
Keywords: Urban Development -- U.K.; Urbanisation -- U.K.